Integrasi Tata Usaha, BMN, SDM, dan Keuangan dalam Sistem Fasilitatif Keimigrasian - Dimas Pramudya Sanjaya; Chefli Chefli; Eunike Leoni Sinaga; Abbyl Mohar Muhammad (Jurnal bintang manajemen, 2025)
This study aims to analyze the integration of administration, state property management, human resources, and finance in supporting a facilitative immigration system. These four aspects are essential pillars for maintaining efficiency, effectiveness, and transparency in public service delivery within immigration institutions. However, their implementation often operates separately, causing inefficiency and delays in administrative decision-making. Using a descriptive-analytical approach based on literature review and regulatory analysis, this study finds that structured collaboration among administrative units strengthens internal coordination and improves service quality for the public. Administration functions as the foundation for documentation and record management, state property supports operational infrastructure, human resources drive organizational performance, and finance ensures program continuity and budget accountability. The integration of these components creates a more adaptive, transparent, and accountable work system to face global challenges, especially in the era of digital public services. The study recommends implementing an integrated information system, enhancing personnel competencies, and optimizing budget planning and supervision to achieve professional and competitive immigration governance.